Changing patterns in clinical–histological presentation and renal outcome over the last five decades in a cohort of 499 patients with lupus nephritis. Issue 9 (5th May 2018) - Moroni, Gabriella; Vercelloni, Paolo Gilles; Quaglini, Silvana; Gatto, Mariele; Gianfreda, Davide; Sacchi, Lucia; Raffiotta, Francesca; Zen, Margherita; Costantini, Gloria; Urban, Maria Letizia; Pieruzzi, Federico; Messa, Piergiorgio; et al.
Abstract : Objectives: To evaluate changes in demographic, clinical and histological presentation, and prognosis of lupus nephritis (LN) over time. Patients and methods: We studied a multicentre cohort of 499 patients diagnosed with LN from 1970 to 2016. The 46-year follow-up was subdivided into three periods (P): P1 1970–1985, P2 1986–2001 and P3 2002–2016, and patients accordingly grouped based on the year of LN diagnosis. Predictors of patient and renal survival were investigated by univariate and multivariate proportional hazards Cox regression analyses. Survival curves were compared using the log-rank test. Results: A progressive increase in patient age at the time of LN diagnosis (p<0.0001) and a longer time between systemic lupus erythematosus onset and LN occurrence (p<0.0001) was observed from 1970 to 2016. During the same period, the frequency of renal insufficiency at the time of LN presentation progressively decreased (p<0.0001) and that of isolated urinary abnormalities increased (p<0.0001). No changes in histological class and activity index were observed, while chronicity index significantly decreased from 1970 to 2016 (p=0.023). Survival without end-stage renal disease (ESRD) was 87% in P1, 94% in P2% and 99% in P3 at 10 years, 80% in P1 and 90% in P2 at 20 years (p=0.0019). At multivariate analysis, male gender, arterial hypertension, absence of maintenance immunosuppressive therapy, increased serum creatinine, and high activity and chronicity index were independent predictors of ESRD. Conclusions: Clinical presentation of LN has become less severe in the last years, leading to a better long-term renal survival.